Gastrópodes e outros invertebrados bentônicos do sedimento litorâneo e associados a macrófitas aquáticas em açudes do semi-árido paraibano, nordeste do Brasil - Abílio, Francisco José Pegado (Universidade Federal de São Carlos, 2002)
The Northeastern region in Brazil is characterized by long dry seasons, and the dams are very important to the people living in this region. In this work two dams in the semiarid of Paraiba State were studied to evaluate the quality of the water for human consumption, through the analysis of the benthonic community in the sediment and associated to aquatic macrophytes. The two dams studied are under different influences, one of them called Bodocongó receive organic wastes discharges from the city of Campina Grande, and is characterized as a hypertrophic system due to the high organic content in its waters. The other dam, called Taperoá II, is subjected to drought after long dry seasons. During the time that the present study was conducted, the dam was subjected to intense drying process, remaining only small pools. As a consequence, the waters of these poolls exhibited high values for the salinity and for the electrical conductivity. Even under different influences, the two dams exhibited similar benthic communities, characterized by a poor diversity of taxonomic groups, with predominance of gastropods, especially Melanoides tuberculata (Thiaridae), representing 80% of the total community. Further studies in the laboratory showed that M. tuberculata possesses high resistance to long periods of desiccation, with the survivors possessing high reproductive capacity that could cause the predominance of this species.
Keywords: Limnologia; Gastrópodes; Invertebrados bentônicos; Açudes do semi-árido; CIENCIAS BIOLOGICAS::ECOLOGIA